A solar-responsive zinc oxide photoanode for solar-photon-harvester photoelectrochemical (PEC) cells. Issue 8 (23rd June 2020) - Dom, Rekha; Govindarajan, Sivakumar; Joshi, Shrikant V.; Borse, Pramod H.
Abstract : Deposition of highly efficient, nanostructured, solar-responsive ZnO (SRZO) photoanode for H2 generation by solution precursor plasma spray deposition technique. In PEC Cell, SRZO shows a STH conversion efficiency of 2.32% as seen by evolved H2 . Abstract : A highly efficient, nanostructured, solar-responsive zinc-oxide (SRZO) photoanode has been achieved by utilization of a versatile solution precursor plasma spray (SPPS) deposition technique. For the first time, it is demonstrated that a front-illumination type SRZO photo-anode fabricated with a ZnO/stainless steel (SS-304) configuration can generate an enhanced photo-electrochemical (PEC) current of 390 μA cm −2, under solar radiation from a solar simulator with an AM1.5 global filter (∼1 sun). The SRZO electrode displayed a solar-to-hydrogen (STH) conversion efficiency of 2.32% when investigated for H2 evolution in a PEC cell. These electrodes exhibited a maximum peak efficiency of 86% using 320 nm photons during incident photon-to-current conversion efficiency measurement. Interestingly, the film lattice of SRZO showed a significant red-shift of 0.37 eV in the ZnO band gap thereby providing solar photon absorptivity to SRZO. Further, an enhanced charge transport property by virtue of increased donor density (∼4.11 × 10 17 cm −3 ) has been observed, which is higher by an order of magnitude than that of its bulk counterpart. Efficient optical absorption of solar photons and higher donor-density of SRZO have been thus attributed to its superior PEC performance.